2017
DOI: 10.1242/jcs.202564
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle myosin IIB regulates epicardial integrity and epicardium-derived mesenchymal cell maturation

Abstract: Nonmuscle myosin IIB (NMIIB; heavy chain encoded by MYH10) is essential for cardiac myocyte cytokinesis. The role of NMIIB in other cardiac cells is not known. Here, we show that NMIIB is required in epicardial formation and functions to support myocardial proliferation and coronary vessel development. Ablation of NMIIB in epicardial cells results in disruption of epicardial integrity with a loss of E-cadherin at cell-cell junctions and a focal detachment of epicardial cells from the myocardium. NMIIB-knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
4
4
1
Order By: Relevance
“…As the formation of cardiac valve structures is highly dependent upon a functional endocardium [ 13 , 52 ], the presence of these structures in EHC mutants supports the hypothesis that endocardial function is not significantly impaired following loss of NMHC IIB. A recently published complementary study has demonstrated that coronary vessel development is impaired when NMHC IIB is deleted specifically within the epicardium [ 53 ], supporting our findings that epicardial abnormalities in EHC mutant mice contribute to defective coronary vessel development.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…As the formation of cardiac valve structures is highly dependent upon a functional endocardium [ 13 , 52 ], the presence of these structures in EHC mutants supports the hypothesis that endocardial function is not significantly impaired following loss of NMHC IIB. A recently published complementary study has demonstrated that coronary vessel development is impaired when NMHC IIB is deleted specifically within the epicardium [ 53 ], supporting our findings that epicardial abnormalities in EHC mutant mice contribute to defective coronary vessel development.…”
Section: Resultssupporting
confidence: 90%
“…Indeed, formation of the atrioventricular valves, a process dependent upon endocardial cushion EMT [ 13 ], is evident in EHC mutant hearts ( S5 Fig ). We have demonstrated that NMHC IIB is the predominant NMHC II isoform in epicardial cells both in vivo and in vitro , and that NMHC IIB is localised to distinct subcellular regions (in agreement with the findings of Lo et al, [ 28 ], and Ma et al, [ 53 ]). Therefore, it may be hypothesised that NMHC IIB plays critical roles in epicardial and cardiac development, which cannot be replaced by other NMHC II isoforms when NMHC IIB function is globally ablated.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations